COMPARING TRIAGE ACCURACY BETWEEN PARAMEDICS IN EMERGENCY DEPARTMENT AND NURSES: A PROSPECTIVE OBSERVATIONAL STUDY - Ahmad Abdulaziz Mohammed Alnazr, ‏Huda Abdulkarim Alhsawi, ‏Abdullah Saad Almufarij, ‏Ahmad Yahya Al-Neami, ‏Abdulkarim Dhafer Alquraishi, ‏Fahad Ali Aati, ‏Tahrer Eid Mahammd Alrowaili, Khalid Yahya Ahmad Alneami (Chelonian Research Foundation, 2022)
Accurate triage is crucial for prioritizing patient care in emergency departments (EDs). This study aims to compare the triage accuracy between paramedics and nurses in the ED setting. A prospective observational study was conducted in the ED of King Khaled Hospital in Hafar AlBatin, Saudi Arabia, from January to December 2022. The study included 1,200 adult patients triaged by either paramedics or nurses using the Canadian Triage and Acuity Scale (CTAS). The primary outcome was the agreement between the assigned triage level and the reference standard, determined by an expert panel. Secondary outcomes included the association between triage accuracy and patient characteristics, presenting complaints, and ED length of stay (LOS). The results showed that paramedics and nurses had similar overall triage accuracy rates (79.2% vs. 81.5%, p=0.289). However, paramedics had higher accuracy for high-acuity patients (CTAS levels 1 and 2) compared to nurses (88.4% vs. 80.2%, p=0.013). Triage accuracy was associated with patient age, presenting complaint, and ED LOS. The findings suggest that paramedics and nurses have comparable triage accuracy in the ED, with paramedics performing better for high-acuity patients. The study highlights the potential role of paramedics in enhancing ED triage and the need for ongoing training and quality improvement initiatives. Keywords: triage accuracy, paramedics, nurses, emergency department, Canadian Triage and Acuity Scale